Integration of Industry Work Culture and Teachers' Internship in Improving the Quality of Learning at Vocational High Schools - Hanifah, Lilik; Yuliejantiningsih, Yovitha; Purwosaputro, Supriyono (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyse the influence of industrial work culture and productive teacher internship programs on the quality of education in public vocational high schools (SMK) in Kendal Regency. A quantitative approach, employing a survey method, was used to involve productive teachers from several selected schools through stratified random sampling. Data were collected using a validated and reliable questionnaire. Data analysis employed multiple linear regression and the F-test to assess the significance of the independent variables' impact on educational quality. The results showed that industrial work culture had a significant effect, contributing 37.72% to educational quality, with innovation as the dominant dimension. The productive teacher internship program also had a significant impact, contributing 20.10%, mainly through supervision and industry support dimensions. Simultaneously, both variables accounted for 57.8% of the variation in educational quality, with the remainder influenced by other factors outside the model. These findings underscore the importance of integrating industrial work culture into the learning process and implementing well-structured teacher internship programs that align with industry needs. The results serve as a reference for formulating strategic policies to enhance the relevance of vocational education in meeting labour market demands.